Rehabilitasi Intra Radicular dan Estetika Sesudah Apeksifikasi dengan Mineral Trioxide Agregat pada Apeks Blunderbluss - Anna Muryani; Opik Taofik Hidayat (Jurnal Material Kedokteran Gigi, 2013)
Root canal treatment in necrosis blunderbluss apices difficult to treat and to obtain a good apical seal. A therapy called apexification is required to induce the formation of a calcified apical barrier. The aim of this case report is to demonstrate apexification blunderbluss apices by the use of mineral trioxide agregat (MTA) as an apical plug and follow up fiber reinforced composite (FRC) after bleaching and direct composite. A 18 year old male patient reported with fractured right central incisor on the incisal with blunderbluss apices and the tooth has brown discoloration. MTA as an apical plug was used after the root canals had been debrided and rinsed with 2,5% NaOCl. Calcium hydroxide paste was placed in the canal before the apical portion of the canal was filled with the MTA apical plug. Bleaching before a FRC was placed in the remaining portion of the canal, core build-up was done and direct composite filled over it. At 6 month follow-up period the clinical and radiographic appearance of the teeth had healed successfully. MTA appears to be a promising alternative to calcium hydroxide apexification because of its superior sealing ability, high biocompatibility, and reduced treatment time. The reinforcement of the composite resins by fibers improves their fracture toughnes and resistance. Bleaching and direct composite to make coronal sealing and tooh color returned to the original color. MTA in apexification is valuable method if the quality of coronal sealing can be enhanced.